Nucleoporin 107 is a prognostic biomarker in hepatocellular carcinoma associated with immune infiltration - Ju‐sen Nong; Xin Zhou; Jun‐qi Liu; Jian‐zhu Luo; Jia‐mi Huang; Hai‐xiang Xie; Ke‐jian Yang; Jing Wang; Xin‐ping Ye; Tao Peng (Cancer Medicine, 2023)
Abstract Objective To assess the diagnostic value and clinical significance of nucleoporin 107 (NUP107) in hepatocellular carcinoma (HCC), and explore the possible mechanisms. Methods The transcriptomic and clinical data of HCC patients were retrieved from The Cancer Genome Atlas (TCGA) and GEO databases. Tissue specimens were collected from HCC patients in the Guangxi area. According to the expression levels and prognostic characteristics of NUP107, ROC curves and nomogram models were constructed using the R package. Results NUP107 was highly expressed in 26 human cancers including HCC, and was associated with advanced HCC staging and worse prognosis. NUP107 showed satisfactory ability to predict the prognosis of HCC patients (AUC >0.8). Results of gene set enrichment analysis (GSEA) further showed that NUP107 was mainly associated with cell cycle‐related pathways such as the cell cycle, DNA replication, G2M checkpoint, E2F target, and mitotic spindle. In addition, NUP107 was also associated with immune infiltration in HCC and showed significant positive correlation with immune checkpoints (PD‐L1 and TIM‐3).